PEMODELAN KEBUTUHAN GIZI PADA BALITA DENGAN ARTIFICIAL NEURAL NETWORK - jajang Jajang; Sylvia Meilani (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2021)
An information on the data is not easily obtained if the data is not presented well. The nutritional needs of toddlers are important to be studied to get an information about growth of these toddlers. This research studied the nutritional needs and its factors by using Artificial neural networks (ANN) model. These factors are toddler's age, gender, weight, height, activity. Nutrition data for children under five years old was obtained from interviews at 47 Posyandu locations. The results showed that the resulting ANN model gave quite good results where the error value generated was 0.024